The Effectiveness of Digital Media on Understanding Mathematical Concepts and Problem Solving Abilities: Systematic Literature Review - Gultom, Johannes; Sembiring, Bertha Oktavika; Apriani, Yuni (Universitas Islam Negeri Sunan Kudus, 2025)
This study aims to examine the effectiveness of digital media on students' conceptual understanding and mathematical problem solving abilities. This research employed a Systematic Literature Review (SLR) approach, drawing data from 33 national and international journal articles that have been identified, evaluated, and categorized based on predefined criteria relevant to the study objectives. The results of this study indicate that (1) the integration of digital media in mathematics learning is effective in enhancing students’ understanding of mathematical concepts and their problem-solving abilities, (2) the combination of digital media with appropriate learning models yields greater effectiveness, (3) the most frequently utilized digital tools are GeoGebra and Lectora Inspire, often integrated with contextual and constructivist approaches, (4) digital media plays a significant role in improving students’ mathematical understanding and problem-solving skills, especially when delivered through interactive multimedia that incorporates diverse learning components and meets the criteria of validity, practicality, and effectiveness for classroom implementation. Penelitian ini bertujuan untuk mengkaji efektivitas media digital dalam meningkatkan pemahaman konsep matematika dan kemampuan pemecahan masalah siswa. Metode yang digunakan dalam penelitian ini adalah Systematic Literature Review (SLR), dengan data diperoleh dari 33 artikel jurnal nasional dan internasional. Sumber-sumber tersebut dipilih melalui proses identifikasi, evaluasi, dan kategorisasi yang ketat berdasarkan kriteria yang telah ditetapkan sesuai dengan tujuan penelitian. Hasil dalam penelitian ini adalah (1) penggunaan media digital dalam pembelajaran matematika efektif dalam meningkatkan pemahaman konseptual dan kemampuan pemecahan masalah siswa; (2) Integrasi model pembelajaran dengan media digital meningkatkan efektivitas keseluruhan proses pembelajaran; (3) Alat digital yang paling sering digunakan adalah GeoGebra dan Lectora Inspire, yang umumnya diterapkan bersamaan dengan pendekatan pembelajaran kontekstual dan konstruktivis; (4) Media digital memainkan peran penting dalam meningkatkan pemahaman matematika dan kemampuan pemecahan masalah, terutama ketika disajikan dalam bentuk multimedia interaktif yang diperkaya dengan berbagai komponen pembelajaran, yang telah divalidasi sebagai praktis, efektif, dan layak digunakan di kelas.